ナンキョク ヒョウショウ ジョウ カンソク キチ ノ タメ ノ セツドウ ケンセツ ニ カンスル イチ シアン - 半貫, 敏夫; ハンヌキ, トシオ; 三橋, 博巳; ミツハシ, ヒロミ; 佐藤, 稔雄; サトウ, トシオ; Hannuki, Toshio; Mitsuhashi, Hiromi; Sato, Toshio (1985)
P(論文) 南極氷床上に建設された観測用建物は, ほとんどの場合耐雪構造体の中に配置され, これら全体が雪面下にある。他方, みずほ基地では掘削した雪洞の中に建物を配置する方式を採っていて, ここでは雪面下の建物を雪圧から保護するための本格的な耐雪構造体はなく, 部分的に雪洞の形を保つための支保工が施されているにすぎない。小規模な基地ではこのみずほ方式が魅力的である。本論文では, この雪洞型の基地をつくる場合の難点である雪洞建設について一つの省力化試案を提出した。それは雪面下で雪洞を掘削するかわりに, 貯雪柵の組み合わせや簡易耐雪構造体を用いて雪面上に建てた建物周辺を覆い, このまわりに雪を積もらせて雪洞にしようというものである。この雪洞建設方法の実現の可能性を確かめるために, 軽量で取り扱いが簡単な網を素材にした貯雪柵の防風, 貯雪性能に関する予備的な風洞模型実験を行った。その結果, 網の防風, 貯雪性能はその充実率φによって大きく影響されるが, 適切な網を選択すれば貯雪柵として十分に役立てられるという感触を得た。現在さらに実験精度を吟味した風洞模型実験を継続している。 Most observation stations on the ice sheet in the Antarctic are constructed as subsurface structures. These subsurface stations are composed of buildings and facilities in the snow shelter having a large strength against snow. Mizuho Station of the Japanese Antarctic Research Expedition is a remarkable example of the small subsurface station in the ice sheet. Buildings and facilities of the observation station are constructed in the snow tunnel with little reinforcements. Since hard work is required to construct a snow tunnel for this type of observation station, an efficient method of snow tunnel construction is examined in this paper. The method proposed in this paper consists of the following procedures : (1) Net-fences are set up around the construction site. (2) The huts are constructed. (3) Snow is controlled to be deposited along the net-fences. (4) The snow deposit will grow thicker along the net-fences. (5) Finally a snow tunnel enveloping the net-fences and the huts will be formed. In order to realize the snowdrift control procedure, preliminary tests on the ability of net-fences to prevent wind and to deposit snow are examined in this paper. It is found that the ability of the net-fences can be explained by the variable φ, which is the density ratio of the net. It will be possible to use the net-fences for the snowdrift control under the condition that the combination of the density ratio of the net and the thickness of the yarn is devised effectively. departmental bulletin paper